NORTH KOREA’S NUCLEAR WEAPON DEVELOPMENT IN REGARDS TO THE PRINCIPLE OF SELF DEFENCE IN INTERNATIONAL LAW - Rahmah Kusumayani (Padjadjaran Journal of International Law, 2020)
Abstract Self defence known as an inherent right that is owned by states to protect its sovereignty from attack by other states. The international rules about self defence do not give any limitation about the type of weapon that can be used by states, including the threat or use of nuclear weapons to act self defence. In Practice, many requirements must be fulfilled by states when they claim the act of self defence. Since 2006, North Korea proclaimed its capability to develop nuclear weapons based on self defence argument. The Security Council concluded that North Korea’s development of nuclear weapon program is a threat to international peace and security and condemned such acts with sanctions based on act 41 UN Charter. The purposes of this study are to examine whether the North Korea’s nuclear program as an act of self defence and the UN Security Council’s sanctions to North Korea are in line with the principle of self defence in international law. The result of this research concludes that North Korea’s nuclear program does not meet the requirements as stated in article 51 UN Charter and customary international law regarding self defence. North Korea can not prove that the United States’ threat is jeopardy, and has a wide and dangerous effect for North Korea. Regarding the Security Council’s primary responsibility to maintain international peace and security, states must report his act of self defence to the Security Council immediately. As therefore, sanctions given by the Security Council are in line with the principle of self defence since North Korea can not fulfil the requested requirements of self defence. Keywords: Act 51 UN Charter, Korean Nuclear Development, Principle of self defence Abstrak Hak untuk menerapkan self defence dimiliki oleh tiap negara untuk melindungi kedaulatannya dari serangan negara lain. Peraturan internasional mengenai self defence tidak membatasi jenis senjata yang dapat digunakan oleh negara, termasuk ancaman dan penggunaan senjata nuklir dalam melakukan tindakan self defence. Dalam prakteknya banyak syarat yang harus dipenuhi oleh negara-negara ketika akan mengklaim tindakan self defence. Sejak tahun 2006, Korea Utara mendeklarasikan kesiapannya dalam mengembangkan senjata nuklir dengan alasan self defence. Dewan Keamanan menganggap bahwa program pengembangan senjata nuklir Korea Utara mengancam perdamaian dan keamanan internasional dan berdasarkan Pasal 41 Piagam PBB, Dewan Keamanan memberikan sanksi kepada Korea Utara. Tujuan penelitian ini untuk mengkaji legalitas pengembangan senjata nuklir di Korea Utara atas tindakan yang diklaim negaranya sebagai self defence serta kesesuaian penerapan sanksi Dewan Keamanan PBB dengan prinsip self defence. Hasil dari penelitian ini menyatakan bahwa program senjata nuklir Korea Utara tidak memenuhi syarat yang terdapat dalam Pasal 51 Piagam PBB maupun hukum kebiasaan internasional terkait self defence. Korea Utara tidak bisa membuktikan bahwa ancaman Amerika Serikat bersifat genting dan nyata menimbulkan efek luas dan berbahaya bagi Korea Utara. Berdasarkan tugas utama Dewan Keamanan dalam menjaga kedamaian dan keamanan internasional, negara-negara harus melaporkan tindakan self defence kepada Dewan Keamanan dengan segera. Berdasarkan uraian diatas, sanksi yang diberikan Dewan Keamanan tidak bertentangan dengan prinsip self defence karena Korea Utara tidak bisa memenuhi hal-hal yang disyaratkan untuk melakukan tindakan self defence. Kata Kunci: Pasal 51 Piagam PBB, Pengembangan Senjata Nuklir Korea Utara, Prinsip Pembelaan Diri